Innovation of Product Competitiveness of Warung Angkringan Based On Ethnographic Perspective - Nawangsih Nawangsih (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
The research activities carried out aim to: Analyze the forms of competitive innovation run by angkringan stall business actors and identify patterns of consumer behavior in angkringan stalls. The research methodology uses qualitative research, ethnographic models. Research informants included: Mbok Rey angkringan stalls, Serlok Lumajang, D Jatayu and Mas Erwin Plaza Lumajang angkringan stalls as well as consumers from each of the angkringan stalls. The results of the study show that innovative forms of product competitiveness run by angkringan stalls include: the use of carts as the hallmark of angkringan stalls that reflect Javanese culture, collaboration on menus for food and drinks by combining traditional and modern concepts, the dominant form of service using the Javanese language to impress more familiar and popular, and the available facilities also support the concept of angkringan stalls, for example, angkringan stalls with traditional concepts, lesehan, garden concepts, cafes and so on. Research findings: the ethnographic concept is able to contribute that culture has an important role in people's lives and activities in running an angkringan stall, as a reflection of the concept of a warung business from Javanese culture or tradition which is inherent in the daily life of the community.